INCREASING THE ADDED VALUE OF CASSAVA (MANIHOT ESCULENTA) THROUGH CULINARY PRODUCT INNOVATION BASED ON AU BAIN MARIE TECHNIQUES IN A COMMUNITY SERVICE PROGRAM - Utami, Nisa Rahmaniyah; Sriwulandari, Tatik; Saleha, Saleha (LPPM Univ. Ibn Khaldun Bogor, 2024)
This community service program aims to enhance the added value of cassava (Manihot esculenta) through culinary product innovation using the Au Bain Marie technique. The activity was conducted on December 5, 2024, in Sukajadi Village, involving 15 participants, including housewives, local MSME entrepreneurs, and youth. Through training, participants were taught the process of transforming cassava into innovative products, such as cassava cakes with a soft texture, superior taste, and high visual appeal. The results showed that the Au Bain Marie technique effectively produces high-quality products that meet modern market demands. Product evaluation scored an average of 4.6 out of 5 on parameters such as taste, texture, appearance, and market potential. Furthermore, this program successfully improved participants' skills in modern food processing and created economic opportunities through cassava-based product diversification. In conclusion, cassava processing using the Au Bain Marie technique can empower the community of Sukajadi Village and support economic sustainability based on local food resources. This program is expected to be replicated in other regions to maximize the potential of local food ingredients and improve community welfare.